Echinococcosis of the liver in Poland – review of the literature and our own clinical material - Respondek, Antonina; Baryła, Maksymilian; Popławska-Ferenc, Aleksandra; Kosieradzki, Maciej; Dybicz, Monika; Gołębiowski, Marek; Tronina, Olga; Rahnama, Mansur; Karpeta, Edyta; Małkowski, Piotr (Clinical and Experimental Hepatology, 2024)
Echinococcosis is considered one of the world’s most dangerous zoonoses, and the tapeworm that causes it is one of the two most dangerous parasites to humans globally. Untreated cases may be associated with as high as 90% mortality. The incidence of this pathology is increasing. The authors present an up-to-date review of the literature on liver echinococcosis; they also present their own material of 73 patients with liver echinococcosis treated in the Department of General and Transplant Surgery since 2019.